Collaboration in TVET : proceedings of the 2nd UPI International Conference on Technical and Vocational Education and Training. Bandung, West Java, Indonesia, 4-5 December 2012 - Dittrich, Joachim [Herausgeber]; Abdullah, Ade Gafar [Herausgeber] (My University, 2013)
Starting in 2010, the Universitas Pendidikan Indonesia (UPI) organises every two years the "UPI International Conference on Technical and Vocational Education and Training". These proceedings contain a selection of the papers presented during the 2nd UPI International Conferene on TVET on December 4th and 5th, 2012. The main conference topic was "Collaboration TVET" including several special, thematic sessions: : (1) the Regional Cooperation Platform on Vocational Teacher Training and Education in Asia; (2) the types of vocational teachers needed; (3) assessment in TVET; and (4) the possibility of organised collaboration between universities, companies and schools in vocational teacher training. (BIBB-Doku)
Keywords: P 3.2 Lehrpersonal; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; I 1 Internationale Berufsbildung; I 2.3.4 Asien; I 2.3.1 Afrika; I 2.2 Europa; I 2.3.5 Australien, Ozeanien; Bildungspersonal; Berufsschullehrer; Lehrerbildung; Anerkennung; Internationale Zusammenarbeit; Asien; Bangladesch; Indien; Indonesien; Laos; Malaysia; Afrika; Nigeria; Europa; Bundesrepublik Deutschland; Ozeanien; Australien